Traditional Uses of Begonia Species (Begoniacae) in Nepal - Rajbhandary, Sangeeta (Journal of Natural History Museum, 2015)
In Nepal Begonia L. is represented by 22 species of which ten species are reported in having ethnobotanical value. The 22 Begonia species including the seven endemic species largely belong to 2 sections, Begonia sect. Diploclinium and Begonia sect. Platycentrum. Most Begonia species occur in eastern and central region, and few species in western region. In this paper, ten species of Begonia mostly used as food, ornamental purpose and for medicine in most parts of Nepal is described. Except for Begonia picta, the ethnobotanical uses of other Nepalese Begonia species have not been reported in any previous literature from Nepal. J. Nat. Hist. Mus. Vol. 27, 2013: 25-34